Pengaruh citra merek dan persepsi harga terhadap keputusan pembelian toyota avanza di auto 2000 cabang Ahmad Yani Surabaya - Pratiwi, Charine Anggun; Aminah, Siti (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Competition in the automotive world is currently increasing when compared to the previous year. The increase refers to the lifestyle and needs of the community. Indonesia has an index of buying interest in cars. wheel. four. which. relatively high. Nowadays, customers are also smarter and more selective in choosing cars so that car companies/producers compete for customers by offering various types of brands, prices, types of vehicles, with..quality.product.good. Therefore, this study aims to determine the effect of brand image and price perception on purchasing decisions for Toyota Avanza at Auto 2000 Branch A. Yani Surabaya. The sample used in this study were Toyota Avanza users who transacted at Auto 2000 Branch A. Yani Surabaya with 60 respondents. The sampling technique used in this study is non-probability sampling with purposive sampling, that is, the sample is selected based on predetermined criteria. The data collection method in this study used a questionnaire. The analysis technique used is Partial Least Square (PLS). Based on the research that has been done, it shows that Brand Image has a positive influence on Purchase Decisions and Price Perception has a positive influence on Purchase Decisions for Toyota Avanza at Auto 2000 branch A. Yani Surabaya.